Effect of Online Psychological Intervention on Burnout in Medical Residents From Different Majors: An Exploratory Study - Wang, Jian; Song, Bijia; Shao, Yun; Zhu, Junchao (Frontiers in Psychology, 2021)
Background: Work-related stress among healthcare professionals poses a serious economic and healthcare burden. This study aimed to investigate the prevalence of burnout as well as anxiety, depression, and stress in medical residents from different majors, and assess the effects of an online psychological intervention on the mental health status of medical residents with a high degree of burnout. Methods: We conducted an online survey that collected information on the demographics, mental health, and burnout conditions of medical residents from Shengjing Hospital. The mental health condition was assessed by the Depression, Anxiety, and Stress Scale (DASS) - 21. Further, burnout was assessed by the Maslach Burnout Inventory (MBI). Medical residents with a total MBI score between 50–75 were selected to receive online psychological intervention for 3 months. Results: Two-hundred and ten medical residents completed the questionnaire, of whom, 63 residents with an MBI score between 50–75 received the 3-month online psychological intervention. Anesthesia residents showed the highest level of depression, anxiety, and stress, and presented with a lower sense of personal accomplishment, higher emotional exhaustion, and higher depersonalization. Furthermore, pediatric residents had the second highest DASS and MBI scores following anesthesia residents. Following the online psychological intervention, negative emotional states and burnout levels were significantly lower among anesthesia and pediatric residents. There were no differences in the level of stress and sense of personal accomplishment pre- and post-online psychological intervention among the different majors. Conclusion: Our findings revealed high levels of burnout, as well as depression, anxiety, and stress symptoms in medical residents, with marked differences among different majors. The online psychological intervention effectively improved emotional exhaustion, and depersonalization,, and relieved the psychological problems such as anxiety and depression in medical residents.